Oral manifestations found among illicit drugs users - Alghamdi, Nizar Abdulaziz; Alghamdi, Ahmad Daifallah; Alotaibi, Sanad Safir; Alzahrani, Turki Abdullah; Albeshri, Nouf Saeed; Albarakati, Nahar Nasar; Najei, Ali Jelan (International Journal Of Community Medicine And Public Health, 2023)
Illicit drug use is an intricate challenge that currently affects an individual's health and overall well-being. This review study provides insight into the availability of information regarding the examination of the signs, treatment approaches, and broader consequences related to health problems among individuals who use drugs. The clinical indicators of drug consumption on oral health encompass issues such as dry mouth (xerostomia), gum problems, teeth grinding (bruxism), and dental cavities. These manifestations contribute to immediate discomfort and elevate the risk of long-term dental complications, underscoring the pressing need for intervention and care. Effective management strategies involve a comprehensive approach, incorporating preventive measures, timely treatment, and a compassionate understanding of the unique challenges faced by drug users. Preventive efforts, such as education and regular dental check-ups, serve as critical components in mitigating the clinical manifestations. Treatment strategies, including restorative procedures and periodontal therapy, play a pivotal role in addressing immediate oral health concerns. However, the management of oral health issues extends beyond the dental chair. Acknowledging the hurdles faced by individuals who use drugs, including economic factors and social prejudice, underscores the significance of adopting a comprehensive approach to providing support and assistance. Integrating oral health services with substance abuse treatment presents a promising avenue for comprehensive healthcare. This collaborative approach addresses oral health issues and acknowledges the bidirectional relationship between substance abuse and oral health. In summary, it is essential to comprehend the relationship between illicit drug use and oral health. By implementing management strategies, we can potentially reduce suffering, improve quality of life, and enhance health for individuals affected by substance abuse. This holistic approach emphasizes the significance of acknowledging and addressing these population’s health requirements within a broader healthcare framework.